ENVIRONMENTAL RISKS OF SHALE GAS PRODUCTION FROM GAS-BEARING AREA OF UKRAINE - Калінінченко, А. В.; Копішинська, О. П.; Копішинський, А. В. (Scientific Progress & Innovations, 2013)
In this article the problem of shortage of natural gas in Ukraine as one of the key factors of national energy security. The present state of the fuel and energy sector, the reasons for shortages of natural gas domestic production, alternative perspectives extract gas from shale. The problems and environmental threats and risks associated with the prospects of development of alternative sources of shale gas on the basis of a detailed analysis of its production technology. Comparisons experience with shale gas extraction in the United States, where the technology used for the first time, and the consequences of violations of environmental safety